Effect of Artemisia annua Extract on Kidney Functions and Histology in Experimental Diabetic Rats - Akoul, Marwa (Indonesian Journal Publisher, 2024)
This study sought to understand the impact of an alcoholic extract of Artemisia annua on kidney function in experimental diabetic rats. For this study, fifty adult male albino rats were randomly assigned to one of five groups: G1 received unrestricted access to food and water. G2: To induce diabetes, a single intravenous injection of STZ (60 mg/kg) is administered. The third group undergoes insulin subcutaneous injections for four weeks after each STZ injection. The fourth group takes Artemisia annua extract orally (by gavage) at a dose of 75 mg/kg for four weeks following each STZ injection. The fifth group takes insulin subcutaneously (by gavage) and Artemisia annua extracts orally (70 mg/kg) for four weeks following each STZ injection. We took blood samples from the orbital sinus to estimate creatinine, urea, uric acid, SOD, GPX, and CAT in the serum. We extracted the kidneys for histopathological investigation after slaughtering the animals. The current results demonstrated a significant reduction in all kidney functions, including creatinine and urea, as well as uric acid, following treatment with insulin, Artemisia annua extract, or a combination of insulin and extract. According to these results, the amount of SOD in G3, G4, and G5 is significantly higher than in G1 and G2. However, there were no significant differences between the groups in the amounts of GPX and CAT. The histopathological results of the kidney in groups G1 and G4 revealed a normal histological appearance. Kidneys of G2 exhibit glomerular atrophy and interstitial hemorrhage. G3 displayed tubular epithelial degeneration, necrosis, mesangial cell hyperplasia, glomerular atrophy, and inflammatory cell infiltration. The kidney of G5 displays blood vessel dilatation, congestion, glomerular atrophy, and acute swelling of epithelial cells. In conclusion, the alcoholic extract of Artemisia annua reduces the kidney function in experimental diabetic rats and can alleviate the histological damage of diabetes on renal tissue.